2023
DOI: 10.1097/aud.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cochlear Implantation Outcomes in a Large German Cohort With a Genetic Etiology of Hearing Loss

Anke Tropitzsch,
Thore Schade-Mann,
Philipp Gamerdinger
et al.

Abstract: Objectives: The variability in outcomes of cochlear implantation is largely unexplained, and clinical factors are not sufficient for predicting performance. Genetic factors have been suggested to impact outcomes, but the clinical and genetic heterogeneity of hereditary hearing loss makes it difficult to determine and interpret postoperative performance. It is hypothesized that genetic mutations that affect the neuronal components of the cochlea and auditory pathway, targeted by the cochlear implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Although numerous recent national and international studies have delved into the utilisation of eHealth for diagnosis and treatment in otolaryngology care, 13 , 21 34 the current state and attitudes of otolaryngology patients towards the sustained use of digital ICT, even in the post-CoViD-19 pandemic era, remain insufficiently understood. This knowledge gap raises legitimate concerns that must be further addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous recent national and international studies have delved into the utilisation of eHealth for diagnosis and treatment in otolaryngology care, 13 , 21 34 the current state and attitudes of otolaryngology patients towards the sustained use of digital ICT, even in the post-CoViD-19 pandemic era, remain insufficiently understood. This knowledge gap raises legitimate concerns that must be further addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there was no discernible increase in the adoption or willingness to embrace digital ICT among patients with ear problems despite the recent emphasis of eHealth developments in otolaryngology on this population. 21 24 , 28 30 , 32 , 50 The overall positive attitude towards the utilisation of online appointment management systems combined with automated reminders, which have already found success in other medical fields and several countries, highlights the considerable potential for increased efficiency in cross-sectoral appointment management and reduced no-show rates. 51 53 These findings indicate the appropriateness of introducing these types of eHealth applications in cross-sectoral care throughout the field of otolaryngology.…”
Section: Discussionmentioning
confidence: 99%
“…Common theories, such as perceptual learning 20 , Gestalt-psychology, or pattern recognition are limited in explaining how such general auditory skills develop or relate to innate abilities. Nevertheless, CI implanted subjects demonstrate both the remarkable flexibility of the human brain to function adequately with distorted input once it has learned complex pattern recognition during normal language acquisition 21 , as well as the unaccounted variability in performance 22 . Recently, Froemke et al showed in deafened rats that neuromodulation of the locus coeruleus is strongly related to plasticity and directly effects the learning rate with a CI 23 .…”
Section: Further Enhancing the Development Of Auditory Skills In CI U...mentioning
confidence: 99%
“…Additionally, the nature of poor performance in a CI-fitted population is not yet understood [27]. For example, recent studies [28][29][30] have devoted considerable effort to showing that various factors-including genetic disposition, aetiology, and comorbidities-have an effect on CI outcome. Furthermore, preoperative audiometric assessment in clinical routine [19] potentially provides prognostic value [20][21][22][23].…”
Section: Application Of Tone Decay Assessment In a Changing Patient P...mentioning
confidence: 99%